Theed study of Ar – Kr equimolar alloy morphology - Danchuk, V. V.; Mysko, N. S.; Solodovnik, A. A.; Strzhemechny, M. A. (Хабаршы. Физика сериясы, 2015)
Solid Binary mixtures of cryocrystals are of considerable interest for many reasons [1]. One of them is the possibility of the compare the experimental results with theoretical predictions. According theoreticalmodel of rare – gas binary alloys proposed by Prigogine [2] the solutions should separate in the pure components below about 40 K. This critical temperature depends on the concentration and is a maximum for an equimolar solution.